2021
DOI: 10.1177/27325016211022805
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Assessment and Review of Artificial Intelligence in Facial Paralysis Analysis: Uncovering the Truth

Abstract: Machine learning is a rapidly growing subset of artificial intelligence (AI) which involves computer algorithms that automatically build mathematical models based on sample data. Systems can be taught to learn from patterns in existing data in order to make similar conclusions from new data. The use of AI in facial emotion recognition (FER) has become an area of increasing interest for providers who wish to quantify facial emotion before and after interventions such as facial reanimation surgery. While FER dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Studies have already shown the utility of commercially available AI facial recognition software in medical and surgical applications, such as quantifying facial paralysis and quantifying aesthetic surgical outcomes preoperative and postoperative facial emotions. 9 , 10 Our study applies similar facial recognition technology; however, we have expanded and customized our technology to analyze sets of soft-tissue landmarks on frontal photographs, from which we are able to extract a myriad of observations such as landmark distances, angles, and ratios. Furthermore, our method does not require uploading subject photographs to online servers, thereby allowing potential expansion to patients in the future under Health Insurance Portability and Accountability Act compliance.…”
mentioning
confidence: 99%
“…Studies have already shown the utility of commercially available AI facial recognition software in medical and surgical applications, such as quantifying facial paralysis and quantifying aesthetic surgical outcomes preoperative and postoperative facial emotions. 9 , 10 Our study applies similar facial recognition technology; however, we have expanded and customized our technology to analyze sets of soft-tissue landmarks on frontal photographs, from which we are able to extract a myriad of observations such as landmark distances, angles, and ratios. Furthermore, our method does not require uploading subject photographs to online servers, thereby allowing potential expansion to patients in the future under Health Insurance Portability and Accountability Act compliance.…”
mentioning
confidence: 99%